Gaya Kepemimpinan Raja Daud: “Kajian Sosio-Historis Terhadap Gaya Kepemimpinan Raja Daud Di Kerajaan Israel Bersatu Berdasarkan Teori Kepemimpinan” - Osian Orjumi Moru (Sekolah Tinggi Teologi Duta Panisal, 2023)
Abstract This paper aims to describe the socio-historical study of King David's leadership style based on leadership theory. The method used in this article is a qualitative method with a hermeneutic approach. The various data obtained in this study were then processed using descriptive analysis techniques. The results of the study show that David's leadership in the United Kingdom of Israel can be classified into the great man theory. This is because David's leadership has a uniqueness that includes several important aspects, namely aspects of faith, tolerance, good moral values, quality obedience values, and consistent humanism. King David's leadership style can also be categorized as charismatic leadership. This leadership style can be seen in the pattern of practical control over monarchical power through the establishment of the priesthood sector, the revitalization of royal literary texts, the nationalization of customary law, and persuasive political-economic communication. Keywords: David; Leadership Style; The United Kingdom of Israel.